تصنيف المحافظات السورية حسب إنفاق الأسر على السلع الغذائية باستخدام التحليل متعدد المتغيرات - عكروش محمد; دريباتي يسيرة; جلمودي دارين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تم في هذا البحث تطبيق بعض أساليب التحليل الإحصائي متعدد المتغيرات من أجل معرفة التفاوت في الإنفاق على السلع الغذائية في المحافظات السورية، يذكر البحث أن هناك تقارب في الإنفاق على السلع الغذائية بين 8 محافظات شكلت العنقود الأول للإنفاق المنخفض وهذه المحافظات هي: (حمص، حماه، إدلب، دير الزور، درعا، القنيطرة، الحسكة، الرقة)، وأيضاً كان هناك تقارب بين 6 محافظات شكلت العنقود الثاني للإنفاق المرتفع. هذه المحافظات هي:(دمشق، ريف دمشق، حلب، اللاذقية، طرطوس، السويداء). طبقت هذه الدراسة طريقة التحليل التمييزي متعدد المتغيرات لتمييز السلع الغذائية التي تساهم بشكل ملحوظ في هذا التفاوت، تظهر النتائج أن مجموعتي (الخبز والحبوب)، (السكر والمربى والعسل والشوكولا والحلوى) تساهم بشكل ملحوظ في التمييز بين المحافظات. This research has applied some methods of multivariate statistical analysis in order to know the disparity in spending on food commodities in the Syrian’s provinces. The research reports that there is convergence in spending on food commodities between eight provinces, which formed the first cluster of low spending. These provinces are : (Homs, Hamah, Idleb, Deir-ez-zor, Dar’a, Quneitra, Al-Hassakeh, AL-rakka), and also there is a convergence between six provinces which formed the second cluster of high spending . These provinces are (Damascus, Damascus rural, Aleppo, Lattakia, Tartous, and AL-Sweida). This study also has applied multivariate discriminant analysis method to discriminate the food commodities that contribute significantly to this disparity. The results show the groups: (the bread and cereals), (sugar, jam, honey, chocolate, and sweet) contribute significantly in the discrimination between the provinces.